EVEN THOUGH WE HAD MANY TRIBES, BUT I AM INDONESIA: VALIDATION OF DUAL IDENTITY SCALE - Shadiqi, Muhammad Abdan; Ulum, Wildan Rusdaul; Milla, Mirra Noor; Muluk, Hamdi (Faculty of Psychology, Diponegoro University, 2020)
Dual identity has an assumption that subordinate group identity (e.g., ethnic and tribe identity) and superordinate group identity (e.g., national identity) can be simultaneously activated. The dual identity concept is important to examine in Indonesia as the country of thousands of tribes. As an initial step, we should adapt and evaluate a dual identity scale so that later it will become a catalyst for future study on the exploration of the association of dual identity and other factors. This study aims to adapt and evaluate the dual identity scale on the Indonesian sample. We tested the measurement through two collecting data, with 775 of total participants (data 1= 338 participants and data 2= 473 participants). The data were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). We found that the dual identity scale had a good fit model and had satisfactory validity and reliability. The validity and reliability of data 2 are better than data 1. In the data 2, each item of items used ‘tribe’ as a form of subordinate identity to replace ‘ethnic’ in the measurement of the data 1. In data 1, this scale had a significant correlation with ethnic and national identity. The result of EFA and CFA proved that the scale is unidimensional (having one factor) and robust to use in the Indonesian sample. The study also found that the use of ‘tribe’ can explain subordinate identity better than